Orthodoxy and Evangelicalism: An Overview of Their Relationship from the Perspective of Moral Values - Buda, Daniel (Religions, 2021)
Orthodox-Evangelical relationships are dominated by proselytism (at least in Eastern Europe and in the former Soviet Union). This is understood as church conversion practiced through unfair means among people who are already Christians, belonging to so-called “historical churches.” However, beyond it, there is a real potential for cooperation using moral values as a starting point. As there is an increasing disagreement between the Orthodox and mainline Protestant on moral values, the Orthodox and Evangelicals might increase their cooperation as they witness traditional values of Christianity. This kind of cooperation might be partially contextual, but it is based on Biblicism, which both Orthodox and Evangelicals share as a core value. As this cooperation, based on shared moral values, certainly has real potential, and has to be used for the good of Christianity, it might also have its limitations. Orthodox Christians and Evangelicals have shared common moral values, but each one of them might interpret the content of these values differently. One of the differences in interpreting and explaining the content of moral values might be given by the different interpretations of what is called church tradition.